2011
DOI: 10.1007/s11099-011-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic properties of Quercus × hispanica Lam. and Q. suber L. under harsh Central European winter conditions

Abstract: In search for new forestation tree species for future Central European climate conditions, Mediterranean evergreen oak taxa are investigated for their summer drought-and winter frost-hardiness. Here we report on the winter performance of the photosynthetic apparatus of Quercus × hispanica Lam. and its evergreen parental species Q. suber L. under extraordinary harsh winter conditions. Both taxa showed a strong decline of photosystem II (PSII) quantum efficiency (F v /F m ) with a concomitant increase in the dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…1C) only showed small or moderate declines in chl content, intermediate between the parental species but more similar to the evergreen parent. Intermediate behaviour of the hybrids during winter has also been found in other parameters (Holland & Br€ uggemann 2011;Pflug & Br€ uggemann 2012). The results of in vitro chlorophyll content analysis correlated significantly with the SPAD data in all taxa except Q. suber due to the similarity of all data points in this taxon.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1C) only showed small or moderate declines in chl content, intermediate between the parental species but more similar to the evergreen parent. Intermediate behaviour of the hybrids during winter has also been found in other parameters (Holland & Br€ uggemann 2011;Pflug & Br€ uggemann 2012). The results of in vitro chlorophyll content analysis correlated significantly with the SPAD data in all taxa except Q. suber due to the similarity of all data points in this taxon.…”
Section: Discussionsupporting
confidence: 57%
“…Earlier studies on Mediterranean oaks in winter found similar results, i.e . the photosynthetic apparatus was practically unaffected as long as temperatures did not decrease below 0 to −5 °C (Holland & Brüggemann ; Pflug & Brüggemann ). In European oaks, the deciduous trait is realised in subgenus Quercus (including Q. robur , Q. frainetto , Q. pubescens ) and Q. cerris , which is part of a sister clade to the evergreen species of the subgenus Ilex (Papini et al .…”
Section: Discussionmentioning
confidence: 99%